The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/13621718.2018.1551853
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and prediction of weld morphology for laser oscillating welding of AA6061 aluminium alloy

Abstract: Effects of oscillating diameter ( D) and frequency ( f) on weld surface and cross-sectional morphologies were investigated in laser welding of AA6061 aluminium alloy with circular beam oscillation. Weld surface was mainly characterised by straight line shape when f > 10 Hz. Weld cross-section transformed from slender nail to irregular shape, dumpy nail, rectangle and crescent shape in sequence with the increase of D and f. A modified model considering material thermal properties was developed to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The transient heat transfer model is validated by the experimental results from the literature [40,50]. A total number of around 800 numerical simulations were carried out which serve as a base for the discussed results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient heat transfer model is validated by the experimental results from the literature [40,50]. A total number of around 800 numerical simulations were carried out which serve as a base for the discussed results.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the smaller volume of the molten pool, weld beads with reduced widths are formed. In the third step, the model is translated from no oscillation to beam oscillation condition for a varying radius of oscillation using experimental data from the literature [50] which is shown in Fig. 5f.…”
Section: Model Validationmentioning
confidence: 99%
“…2 of 11 et al [23] investigated the influences of beam oscillating parameters on the weld appearance during the laser welding of austenitic stainless steel. Wang et al [24,25] found that beam oscillation stabilized the process and improved weld morphology. Furthermore, the elongation of welds was increased.…”
Section: Appl Sci 2019 9 X For Peer Reviewmentioning
confidence: 99%
“…Hao et al [11] showed the effects of laser beam oscillation parameters on the laser-welded austenitic stainless steel joints. Wang et al [12,13] stated that the laser beam oscillation stabilized the welding process and improved the welding morphology. Kuryntsev and Gilmutdinov [14] investigate the influence of the second wobbling laser welding pass on microstructure and mechanical properties of structural steel.…”
Section: Introductionmentioning
confidence: 99%